Analisis Prioritas Rehabilitasi Bendung:Studi Kasus Bendung Cokrobedog, Gamping, Pendowo dan Pijenan di Kali Bedog - Putri, Nanda Melyadi (Semesta Teknika, 2018)
The government provided Special Allocation Budget via APBD for rehabilitation activities in order to increase the function and physical condition of the weirs. The rehabilitation performances must be run stage by stage due to the limitation of allocation budget, however, it would be continual. Hence the analysis of rehabilitation priority was needed. The case study of this research was the determination of rehabilitation priority towards the weirs of Cokrobedog, Gamping, Pendowo, and Pijenan. These four weirs were at Kali Bedog, Daerah Istimewa Yogyakarta.The method used for priority analysis in this research was Multi Attribute Decision Making method (MADM), consisted of AHP, ELECTRE, SAW, TOPSIS, and WP. The criterias used were the infrastructure conditions, the availability of water, and the command areas by the percentage weighting of assessment criteria at 57 , 29 and 14. The damage percentage of Gamping was 44.66%, ranked as serious damage. The damage percentage of Cokrobedog, Pendowo and Pijenan for each of it was 36.11%, 33.57% and 30.30%, ranked as average damage. The order of priority rehabilitation of dams tend not begin with the largest command area. TOPSIS method is a method most appropriate MADM applied in the prioritization of rehabilitation because it has a significantly different end value.